THE GROWTH OF MICRO, SMALL AND MEDIUM-SIZED HOTEL ENTERPRISES: THE HOTELIERS' PERSPECTIVES - Awang, Khairil Wahidin; Abdul Aziz, Yuhanis; Samdin, Zaiton (Journal of Technology Management and Business, 2015)
Kelantan, considered a peripheral state in Malaysia, is economically driven by hordes of small and medium-sized enterprises. The existence of many micro, small and medium-sized hotel enterprises (MSMEs) in Kelantan indicates the important role they play in expounding Malaysia’s tourism industry, therefore the focus of this paper. Eleven hoteliers representing such enterprises were interviewed using face-to-face in-depth interview technique. Researchers also interviewed several policy makers. Findings suggest that many of the micro and small enterprises faced daunting task of raising capital to sustain or expand their businesses. The medium-sized enterprises on the other hand were more fortunate in the sense that the higher number of rooms they operated ensured a higher income, therefore, relatively easier for them to raise capital when situation arisen.